10.1177/1056789514562152 (CrossRef Listing of Deleted DOIs, 2015)
Medical care delay or avoidance (MCDA) has negative consequences for both individuals and society. This study moves beyond a descriptive account of factors associated with MCDA and examines potential indirect pathways related to MCDA. Specifically, we hypothesize that medical distrust and desire to not always follow rules are indirectly and positively associated with MCDA through the endorsement of alternative norms supporting MCDA. A sample of 425 participants completed an online survey. The analysis showed that higher medical distrust and stronger desire to not follow rules were associated with greater endorsement of alternative norms supporting MCDA, which, in turn, was associated with greater MCDA. These findings highlight the importance of addressing alternative normative beliefs in public health initiatives aimed at shifting perceptions of medical care and promoting adequate medical care utilization. Interventions aimed at reducing MCDA may be more effective if they also target medical distrust and desire to not follow rules.